Draft genome sequence of Inquilinus limosus strain MP06, a multidrug-resistant clinical isolate - Pino, Marylú (2015)
The bacterium, Inquilinus limosus, with its remarkable antimicrobial multiresistant profile, has increasingly been isolated in cystic fibrosis patients. We report draft genome sequence of a strain MP06, which is of considerable interest in elucidating the associated mechanisms of antibiotic resistance in this bacterium and for an insight about its persistence in airways of these patients.